2017
DOI: 10.1159/000477815
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Managed Pediatric Intracranial Aneurysms: How Different Are They from Adult Intracranial Aneurysms?

Abstract: Purpose: Intracranial aneurysms in children are rare compared to those in adults, and their causes, presentations, and outcomes also vary. Thus, they need to be studied intricately and as an independent entity. Methods: We retrospectively reviewed intracranial saccular aneurysms in 44 children of <19 years of age who had been surgically treated during the last 30 years at our institute. We analyzed presentation, characteristics, size, multiplicity, cause, and eventual outcome, and compared these to the adult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Brain aneurysms affect almost exclusively the adult population [1], and its incidence in children is rare [1][2][3][4][5][6][7][8][9][10], accounting for less than 5% of all aneurysms [1-3, 5, 7, 8, 11, 12]. Also, compared to adults, they are more complex [4,10] and differ in location, morphological characteristics, the presentation, and outcome [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Brain aneurysms affect almost exclusively the adult population [1], and its incidence in children is rare [1][2][3][4][5][6][7][8][9][10], accounting for less than 5% of all aneurysms [1-3, 5, 7, 8, 11, 12]. Also, compared to adults, they are more complex [4,10] and differ in location, morphological characteristics, the presentation, and outcome [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Undiagnosed patients with un-ruptured intracerebral aneurysms can present with a neurological or neuropsychiatric illness like a migraine without aura, focal and generalized seizures, frontal lobe syndrome, and visual impairment [6]. Intracranial internal carotid artery aneurysm may present with diplopia, retroorbital pain, and unilateral headache mimicking migraine without aura.…”
Section: Discussionmentioning
confidence: 99%
“…Ruptured aneurysms present with subarachnoidal hemorrhage (SAH) and intracerebral/intraventricular or subdural hemorrhage. SAH is by far the most common symptom in the majority of pediatric intracranial aneurysm case series [2-9]. In recent clinical reviews by Sorteberg and Dahlberg [1], Regelsberger et al [10], and Huang et al [11], the average SAH presentation rates were reported as 72, 77, and 80%, respectively.…”
Section: Discussionmentioning
confidence: 99%